Preučevanje vplivov različnih parametrov na učinkovito odstranjevanje ionov iz vodnih raztopin z membransko kapacitivno deionizacijo - Biro, Miša (visokošolska dela, 2015)
In industry for the majority of technological processes fresh and high quality water is required. The amount of used water, which is at the end of each process actually a waste water, is very large and burdensome for the environment. Therefore, in the industry different technologies for waste water treatment are used, with aim that treated water could be re-used in different technological processes. The requirements for the water quality, which can be applied to the individual procedures, are clearly defined. For example, in textile industry one of the requirements is the conductivity of the water, which must be lower than 1.5 mS/cm. In comparison to the conductivity of potable water, which has a conductivity of 0.550 mS/cm, the conductivity of textile water can be quite high - depending on the process operation up to 115 mS/cm. In our dissertation we studied the effects of various parameters on the effective desalination on model and real water samples using membrane capacitive deionization, a low-pressure electrochemical process, by which in the presence of an electric field the ions are removed from the electrolyte. 363 model samples and waste water samples from textile industry with different initial conductivities, different composition and operational conditions (duration of regeneration and desalination phase, flow applied in the regeneration and desalination phase, duration of device operating time) were included in the study. The purpose of the study was to determine how different parameters affect the efficiency of membrane capacitive deionization and to establish the optimal conditions for the system operation. With atomic emission and atomic absorption spectrometry, inductively coupled plasma with optical emission and mass spectrometry and with ion chromatography the concentration of ions were determined in individual samples, which were collected during operation of membrane capacitive deionization. By analyzing the results of measurements we determined the efficiency of desalination, i.e. removal of ions from samples. The results showed that the concentration of ions during the process of wastewater treatment with membrane capacitive deionization in some cases significantly reduced already after a few minutes of system operation. In addition we carried out the chemometrical characterization of samples. The purpose of the study was to determine whether there exist significant differences between samples, to search for correlations between monitored parameters: the presence of various ions, desalination and water recovery, the duration of each phase and the flow of the solution in each phase. We performed a correlation analysis, analysis of variance (ANOVA), Mann Whitney test, principal component analysis (PCA), cluster analysis (CA) and multiple linear regression (MLR). With multiple linear regression we built 3 models and established that model values fit very well to experimental values.
Keywords: chemometric characterisation; chemometric classification; cluster analysis; conductivity; desalination efficiency; Disertacije; hierarhično razvrščanje; kemometrijska karakterizacija; kemometrijska klasifikacija; membrane capacitive deionization; membranska kapacitivna deionizacija; metoda glavnih osi; multiple linear regression; Odpadne vode; prevodnost; principal component analysis; Razsoljevanje; učinkovitost razsoljevanja; večfaktorska linearna regresija; waste water treatment